Frederick Wiseman ruptura e transformações no cinema documentário - Weller, Fernando (2008)
The present dissertation investigates transformations undergone by the field of documentary cinema, especially from the sixties onwards, as of the emergence of Direct Cinema and Cinéma Vérité. The analysis subject is the work of American filmmaker Frederik Wiseman and its central role in the weakening process of the hegemonic documentary order, established during the 2nd world war. We brought under more detailed scrutiny the film Titicut Follies (1967), bringing to attention its narrative and dramatic aspects and its critical positioning towards power relations in the documented institution.